Dependence and mechanism of hydrogenation behavior on absorption conditions in hypo-eutectic Mg–Ni–Cu alloy. (23rd August 2018) - Ding, Xin; Chen, Ruirun; Chen, Xiaoyu; Li, Xinzhong; Guo, Jingjie; Su, Yanqing; Ding, Hongsheng; Fu, Hengzhi
Abstract: In this article, the isothermal hydrogenation curves of hypo-eutectic Mg–6Ni–3Cu (at. %) alloy under various temperatures and applied hydrogen pressures are fitted by Johnson-Mehl-Avrami equation. The hydrogenation behavior and its dependence on absorption conditions are investigated, as different from that of pure Mg. A three-stage hydrogenation behavior is illustrated and an extra absorption process (Stage III) resulted from H dissolution or the hydride formation in boundaries appears when the hydrogen pressure reaches a critical value. Due to the same role of increased Δ P and decreased Δ T on hydride nucleation driving force and their opposite impacts on H diffusion, temperature and hydrogen pressure are influencing the absorption process differently. As the great H permeability in Mg–Mg2 Ni–Mg2 Cu eutectic, more hydrogen is absorbed under larger hydrogenation driving force, rather than hydrogen uptake deficit. It is revealed that the reaction order η corresponding to H diffusing in thin MgH2 layer is larger than that in thick MgH2 shell, which can preliminarily identify the hydrogenation behavior after MgH2 impinging around primary Mg (Stage II). Graphical abstract: Image 1 Highlights: Hypo-eutectic Mg–6Ni–3Cu alloy shows a different absorption behavior from pure Mg. Temperature and hydrogen pressure affect the hydrogenation behavior differently. More H is absorbed under faster initial nucleation rate for Mg–6Ni–3Cu alloy. The η value in Stage II corresponding to H diffusing in a thinner MgH2 layer is larger.